OPTIMALISASI PENGELOLAAN DAYA TARIK WISATA (DTW) PADA MASA PANDEMI OLEH DISPORAPAR KABUPATEN KENDAL - Suwarji Suwarji; Maulida Putri Rahmawati (Universitas Halu Oleo, 2021)
The purpose of this research is to analyze and describe how optimalization management of tourist attraction during pandemic by Dinas Kepemudaan, Olahraga dan Pariwisata Kendal Regency. This study uses a descriptive qualitative method, which means that researchers get data through observation and interviews and documents about Tourist Attractions by Disporapar. The data analysis used the theory of Miles & Huberman which consists of data reduction, data presentation, and conclusion. The results showed that Disporapar held tourism management training for tourism actors with the aim that tourism actors were able to make Kendal Regency tourist destinations known to tourists and the wider community during the pandemic. The optimization of the management of Tourist Attractions during the pandemic by Disporapar has gone well and effectively. Such as providing a place to wash hands, adjusting seating distances and requiring visitors to wear masks. Disporapar worried if this pandemic will be long over, because it affects the income of business actors.